Novel Foveal Features Associated With Vision Impairment in Multiple Sclerosis - Hargrave, Aubrey; Sredar, Nripun; Khushzad, Fareshta; Yarp, Jennifer; Tomczak, Anna; Han, May; Kipp, Lucas; Dubra, Alfredo; Moss, Heather E. (Investigative ophthalmology & visual science, 2021)
To characterize scattering and hyperreflective features in the foveal avascular zone of people with multiple sclerosis (MS) using adaptive optics scanning laser ophthalmoscopy (AOSLO) and to evaluate their relationship with visual function and MS disease characteristics. Twenty subjects with MS underwent confocal reflectance and non-confocal split-detection AOSLO foveal imaging. Peripapillary retinal nerve fiber layer thickness was measured using optic nerve optical coherence tomography. Blood pressure, intraocular pressure (IOP), and best-corrected high-contrast visual acuity (HCVA) and low-contrast visual acuity (LCVA) were measured. AOSLO images were graded to determine the presence and characteristics of distinct structures. Two distinct structures were seen in the avascular zone of the foveal pit. Hyperreflective puncta, present in 74% of eyes, were associated with IOP and blood pressure. Scattering features, observed in 58% of eyes, were associated with decreased HCVA and LCVA, as well as increased MS duration and disability, but were not associated with retinal nerve fiber layer thickness. Hyperreflective puncta and scattering features were simultaneously present in 53% of eyes. Hyperreflective puncta were associated with parameters affecting ophthalmic perfusion, but they were not associated with MS disease parameters. Scattering features were associated with parameters corresponding to advanced MS, suggesting that they may be related to disease progression. Scattering features were also correlated with reduced visual function independent from ganglion cell injury, suggesting the possibility of a novel ganglion cell-independent mechanism of impaired vision in people with MS.